Quando gafanhoto significa relâmpago: como o conhecimento ecológico é codificado nas línguas ameaçadas - Stringer, David (Ecolinguística: Revista brasileira de ecologia e linguagem (ECO-REBEL), 2018)
In response to world-wide extinction of both indigenous languages and endemic species, an international, interdisciplinary movement has arisen with the goal of conserving biocultural diversity. The fundamental insight of biocultural conservation initiatives is that established correlations between cultural diversity and biodiversity (and endangerment) may point to solutions to the present crisis. This paper highlights one understudied aspect of this endeavor ”“ how ecological knowledge is encoded in endangered languages ”“ before considering how linguists may contribute to this growing community of practice. The most obvious linguistic encoding of traditional ecological knowledge is in the mental lexicon: words that refer to objects, events, and states in the natural world, as shown in examples drawn from languages such as Kayapó, Piaroa, and Minangkabau. Equally important for the linguistic transmission of ecological knowledge are the narratives found in stories, myths and ceremonial recitation, as exemplified by Chehalis, Wayampi, and Bininj Gunwok. Linguists who join this interdisciplinary struggle for environmental conservation and social justice may contribute not only through primary fieldwork, linguistic analysis, or expertise in multilingual education programs, but also by raising consciousness of the beauty and value of biocultural diversity through social outreach.